A Study on the Influence Effect of Digital Investment on the Environmental Performance of Listed Companies - Huang, Tianxiao (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of the digital economy and the continuous promotion of the green development strategy, whether the digital investment of enterprises can enhance their environmental performance has become an urgent issue to be explored. Taking A-share listed companies in China from 2017 to 2022 as a sample, this paper empirically analyzes the effects of digital investment on corporate environmental performance and the heterogeneity characteristics, and tests the mediating roles of agency costs and green technology innovation. It is found that digital investment can significantly enhance the environmental performance of listed companies, and the results of robustness test show that this conclusion still holds. In terms of the mechanism of action, digital investment will enhance the environmental performance of listed companies by reducing agency costs and promoting corporate green technology innovation. Heterogeneity analysis shows that digital investment can significantly improve the environmental performance of non-state-owned enterprises and non-heavily polluted enterprises. The conclusion enriches the research related to digital investment and corporate environmental performance, and also provides some references on how to improve the environmental performance of listed companies.